A low‐profile dual‐band multimode patch antenna for wireless local area network and cellular vehicle‐to‐everything communications. Issue 12 (13th September 2021) - Zhao, Chen; Xu, Huan; Wang, Yang; Zhu, Xicheng
Abstract: In this article, a low‐profile dual‐band patch antenna for vehicle communication is proposed. With two sets of shorting vias on the hexagonal‐shaped patch at different positions and single feed at the center, three different resonant modes are excited, forming two operating bands with omnidirectional and conical beam radiation respectively. The omnidirectional radiation at 2.45 GHz is used for wireless local area network (WLAN) communication while the conical beam radiation is used for cellular vehicle‐to‐everything (C‐V2X) communication. The proposed antenna is fabricated using the printed circuit technique. Both the measured reflection coefficient and radiation pattern match well with the simulations. With the advantage of low profile, dual‐band, and dual radiation characteristics, the antenna owns a good potential to be used in vehicle communications.